Cover Feature: Spectroscopic Investigation of Chalcogen Bonding: Halide–Carbon Disulfide Complexes (ChemPhysChem 9/2021). Issue 9 (5th May 2021) - Haakansson, Christian T.; Corkish, Timothy R.; Watson, Peter D.; Robinson, Hayden T.; Tsui, Terrence; McKinley, Allan J.; Wild, Duncan A.
Abstract : The Cover Feature shows an archetypal chalcogen bond stabilising the dimer complex between carbon disulfide and a halide anion (artwork: Christian and Elham Haakansson). Laser light is utilised to detach electrons from the complex in order to discern chalcogen binding energy in combination with high‐level ab initio calculations. More information can be found in the Communication by Duncan A. Wild and co‐workers .